2002
DOI: 10.1038/sj.onc.1205981
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the IRF-1 tumour modifier during the response to genotoxic stress involves an ATM-dependent signalling pathway

Abstract: The mechanism by which genotoxic stress induces IRF-1 and the signalling components upstream of this antioncogenic transcription factor during the response to DNA damage are not known. We demonstrate that IRF-1 and the tumour suppressor protein p53 are coordinately up-regulated during the response to DNA damage in an ATM-dependent manner. Induction of IRF-1 protein by either ionizing radiation (IR) or etoposide occurs through a concerted mechanism involving increased IRF-1 expression/synthesis and an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 60 publications
1
62
0
Order By: Relevance
“…The onset of IRF1 protein induction by 24-h BrdU þ DMA treatment correlated with the induction of IFNb expression (Figure 2b), indicating that IRF1 occurs in early phases of interferon gene induction and, together with IRF7, can participate in the persistent activity of the IFN-JAK/STAT pathway in cells undergoing BDIS. In addition, we found elevated IRF1 in HeLa cells brought to senescence using camptothecin, etoposide (see also Pamment et al, 2002), doxorubicin, APH and HU (data not shown). Overall, the upregulation of transcripts of several ISGs indicated that BrdU þ DMA-induced activity of interferon-JAK/STAT signaling results in corresponding gene expression.…”
Section: Activation Of Ifn Pathway In Genotoxic Stressmentioning
confidence: 72%
“…The onset of IRF1 protein induction by 24-h BrdU þ DMA treatment correlated with the induction of IFNb expression (Figure 2b), indicating that IRF1 occurs in early phases of interferon gene induction and, together with IRF7, can participate in the persistent activity of the IFN-JAK/STAT pathway in cells undergoing BDIS. In addition, we found elevated IRF1 in HeLa cells brought to senescence using camptothecin, etoposide (see also Pamment et al, 2002), doxorubicin, APH and HU (data not shown). Overall, the upregulation of transcripts of several ISGs indicated that BrdU þ DMA-induced activity of interferon-JAK/STAT signaling results in corresponding gene expression.…”
Section: Activation Of Ifn Pathway In Genotoxic Stressmentioning
confidence: 72%
“…IRF-1 is thought to undergo posttranslational modification to activate IFN-stimulated genes (33), and IFN-g-induced tyrosine phosphorylation of IRF-1 leads to activation (34). Recently, it was shown that IRF-1 expression (mRNA and protein) and protein stability were controlled by an ATM signaling pathway in response to irradiation (9). Whereas IRF-5 is phosphorylated and activated by viral infection (21,22) or by stimulation with the toll-like receptor-7/8 inducer resiquimod (R-848; ref.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to tumor suppressor activity, IRF-1, in particular, has received much attention over the past 10 years. Regulation of IRF-1 is thought to be controlled by two distinct signaling pathways; a Janusactivated kinase (JAK)/signal transducers and activators of transcription (STAT) signaling pathway in virus-infected or IFNtreated cells and an ataxia telangiectasia mutated (ATM) signaling pathway in DNA-damaged cells (9). Genes downstream of IRF-1 in these two pathways include IFNB (10, 11), RNA-dependent protein kinase (12, 13), 2-5A synthetase (14,15), cyclin-dependent kinase inhibitor p21 (WAF1/CIP1; refs.…”
Section: Introductionmentioning
confidence: 99%
“…30 Since overexpression of IRF1 leads to elevated PML transcripts, 80 increased levels of IRF1 found after drug treatment 35 may contribute to JAK/STAT-dependent PML expression in our present study. Moreover, ATM-dependent stabilization of IRF1 was reported after etoposide treatment, 81 and precise characterization sensitivity of BrdU-treated cells to light-induced DNA damage, cells were exposed to light only for minimal time periods necessary for handling. Senescence associated-β-galactosidase assay was performed as described 86 with modifications described in.…”
Section: Discussionmentioning
confidence: 99%